Investigating Post-Task Responses using MEG and 7T fMRI - Coleman, Sebastian C. (2024)
Electrophysiology and haemodynamics related to human brain function can be measured using several modern imaging techniques. Magnetoencephalography (MEG) enables direct measurement of neuromagnetic fields created by signal transmission in neuronal ensembles, with high temporal resolution but limited spatial resolution and depth sensitivity. Functional magnetic resonance imaging (fMRI) enables the indirect measurement of neuronal activity through changes in blood oxygenation, with lower temporal resolution but high spatial specificity throughout the entire brain. These techniques can be used to investigate the spatial origin and dynamics of brain activity, in response to tasks or during resting state. This thesis uses MEG and fMRI to study responses that occur in the transition period between task cessation and rest, which we term post-task responses (PTRs).